Spatial Misallocation, Informality, and Transit Improvements : Evidence from Mexico City - Zárate, Román D. (World Bank, Washington, DC, 2022)
This paper proposes a new mechanism to explain resource misallocation in developing countries: the high commuting costs within cities that prevent workers from accessing formal employment. To test this mechanism, the paper combines a rich collection of microdata and exploits the opening of new subway lines in Mexico City. The findings show that transit improvements reduce informality by 7 percent in areas near the new stations. The paper develops a spatial model that accounts for the direct effects of infrastructure in perfectly economies and allocative efficiency. Changes in allocative efficiency driven by workers’ reallocation to the formal sector amplify the gains by 20–25 percent.